Investigating the Time Course of Part-Based and Holistic Processing in Face Perception - Wang, Chao-Chih (Frontiers in Psychology, 2019)
Face recognition is an extraordinary ability for humans and provides a distinct contrast between biological and artificial computational systems. In the present experiments, the exposure duration was manipulated to examine the time course of face processing and found evidence suggesting that holistic processing occurs shortly after part-based processing at about 200 ms, and can last for a relatively long duration up to 2,000 ms. These results lent support to a dual-route model comprising holistic processing and part-based processing in face perception. However, our findings were inconsistent with the previous study which suggests that no holistic processing was observed at the relatively long duration, and suspected that perceptual discriminability may have been responsible for the discrepancy.